Exploring the structure-activity relationship of benzylidene-2,3-dihydro-1H-inden-1-one compared to benzofuran-3(2H)-one derivatives as inhibitors of tau amyloid fibers - Boukherrouba, Emeline; Larosa, Camille; Nguyen, Kim-Anh; Caburet, Jérémy; Lunven, Laurent; Bonnet, Hugues; Fortuné, Antoine; Boumendjel, Ahcène; Boucherle, Benjamin; Chierici, Sabine; Peuchmaur, Marine (European journal of medicinal chemistry, 2022)
Tauopathies, such as Alzheimer's disease, have been the subject of several hypotheses regarding the way to treat them. Hyperphosphorylation of tau protein leading to its aggregation is widely recognized as a key step in the development of these diseases resulting in neuronal dysfunction. The AcPHF6 model of tau that includes the shorter critical fragment involved in the protein aggregation was used in vitro to identify new potential inhibitors. Following a previous study on aurone derivatives, we herein compare this polyphenol family to a very close one, the benzylidene-2,3-dihydro-1H-inden-1-one (also named indanone). The structure activity relationship studies bring to light the importance of the hydroxylation pattern in both series: the more hydroxylated, the more active. In addition, the three-dimensional shape of the molecules is involved in their interaction mode with their target, thus defining their role either as inhibitors of fiber elongation or as fiber-binding molecules. Indanone 13a was identified as a promising inhibitor: its activity was confirmed by circular dichroism and atomic force microscopy studies. [Display omitted] •Polyhydroxylated indanone identified as inhibitors of the aggregation of a tau model.•Importance of the substitution pattern to optimize interactions with the tau model.•Three-dimensional shape is a major parameter in indanone activity.